Development of perceptual inhibition in adolescents— a critical period? - Introzzi, Isabel Maria (2021)
Recent studies suggest that the developmental curves in adolescence, related to the development of executive functions, could be fitted to a non‐linear trajectory of development with progressions and retrogressions. Therefore, the present study proposes to analyze the pattern of development in Perceptual Inhibition (PI), considering all stages of adolescence (early, middle, and late) in intervals of one year. To this aim, we worked with a sample of 275 participants between 10 and 25 years, who performed a joint visual and search task (to measure PI). We have fitted ex‐Gaussian functions to the probability distributions of the mean response time across the sample and performed a covariance analysis (ANCOVA). The results showed that the 10‐ to 13‐year‐old groups performed similarly in the task and differ from the 14‐ to 19‐year‐old participants. We found significant differences between the older group and all the rest of the groups. We discuss the important changes that can be observed in relation to the nonlinear trajectory of development that would show the PI during adolescence.